Investments into Community Social Activities: Implications for Selected Johannesburg Stock Exchange Listed Companies - Moswatsi, Kgorompe Michael; Kanjere, Maria Matshidiso (Acta Universitatis Danubius. Œconomica, 2023)
Investment into community social activities CSA) has a lot of implications for companies. This is because investors value companies that take Corporate Social Responsibility (CSR) seriously. Furthermore, companies that invest into community social activities enjoy long lasting relationship with their customers. Therefore, this article is based on the research that was conducted on selected Johannesburg Listed Companies. The aim of the research was to investigate if there is correlation between investment in community social activities (CSA) and organisations financial performance (ROA) of the companies listed on the Johannesburg Stock Exchange JSE SRI Index. The study used the quantitative research method. The multiple linear regression analysis, which utilised the panel data was applied to analyse the integrated annual reports of 175 Johannesburg Stock Exchange listed organisations for the period 2009 to 2019. The researcher discovered that when organisations have the right relationship with the surrounding communities, they turn to have an on-going consumer relationship. Again, the researcher found that good consumer relationships through patronage by the community will, in turn, improve the organisations’ financial performance. The results of the study create an important platform to add to the practice of community social activities by encouraging Johannesburg Stock Exchange listed organisations to integrate their community social responsibility policies into their strategic goals. The researcher recommends future researchers to use all Johannesburg Stock Exchange socially responsible investment Index listed organisations to assess the influence of sustainability performance on organisations’ financial performance.